Environmental Tax Reform in a Federation with Rent-Induced Migration - Jean-Denis Garon; Charles Séguin (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study the welfare effects of a revenue-neutral green tax reform in a federation. The reform consists of increasing a tax on a polluting input and reducing that on labor income. Households are fully mobile within the federation. Regions are unequally endowed with a nonrenewable natural resource. Resource rents are owned by regions and are redistributed to citizens on a residence basis, which generates a motive for inefficiently relocating to the resource-rich jurisdiction. Since the resource-poor region has a higher marginal product of labor than does the resource-rich region, the tax reform mitigates the scope of inefficient migration. This positive welfare effect may significantly reduce abatement costs of pollution and calls for higher environmental tax, as compared with a model where migration is assumed away.
Keywords: D62; H21; H23; H77; 330; federalism; environment; taxation; equalization; mobility; externalities